Integration of Ecotheology in Islamic Religious Education - Ferniati Misa; Ima Fitasari; Nasrina Nasir; Wa Dilan (International Journal on Advanced Science, Education, and Religion, 2026)
This study examines the integration of ecotheology in Islamic Religious Education (PAI) as a strategic effort to strengthen an ecologically-minded school culture amidst the global environmental crisis. The background of this study is rooted in the increasing urgency of education that is not only oriented towards religious cognitive aspects, but also on the internalization of the values ​​of sustainability and ecological responsibility in Islamic educational practices. The main objective of this study is to analyze the interaction between Islamic theological values ​​and ecological awareness that shape environmentally friendly pedagogical practices in Islamic educational institutions. The approach used is qualitative with a thematic analysis strategy through the processes of coding, triangulation, meta-analysis, and meta-synthesis of various empirical data and academic literature. The results of the study indicate that the values ​​of tauhid, khalifah, and amanah can be used as an epistemological and pedagogical foundation in developing a learning model oriented towards environmental sustainability. The integration of ecotheology into the PAI curriculum can create a more contextual ecological awareness, harmoniously combining spiritual, social, and ecological aspects. The contribution of this research lies in affirming the importance of an ecotheology-based Islamic education paradigm as a transformative approach to building the character of students who are faithful, knowledgeable, and ecologically ethical in facing the challenges of modern civilization.